Charge‐Trap Memory Based on Hybrid 0D Quantum Dot–2D WSe2 Structure. Issue 20 (17th April 2018) - Hou, Xiang; Zhang, Heng; Liu, Chunsen; Ding, Shijin; Bao, Wenzhong; Zhang, David Wei; Zhou, Peng
Abstract: Recently, layered ultrathin 2D semiconductors, such as MoS2 and WSe2 are widely studied in nonvolatile memories because of their excellent electronic properties. Additionally, discrete 0D metallic nanocrystals and quantum dots (QDs) are considered to be outstanding charge‐trap materials. Here, a charge‐trap memory device based on a hybrid 0D CdSe QD–2D WSe2 structure is demonstrated. Specifically, ultrathin WSe2 is employed as the channel of the memory, and the QDs serve as the charge‐trap layer. This device shows a large memory window exceeding 18 V, a high erase/program current ratio (reaching up to 10 4 ), four‐level data storage ability, stable retention property, and high endurance of more than 400 cycles. Moreover, comparative experiments are carried out to prove that the charges are trapped by the QDs embedded in the Al2 O3 . The combination of 2D semiconductors with 0D QDs opens up a novelty field of charge‐trap memory devices. Abstract : Hybrid 2D WSe2 –0D CdSe quantum dot (QD) structural charge‐trap memory is demonstrated, with WSe2 as the channel and CdSe QDs as the charge‐trap layer. The fabricated devices exhibit ideal nonvolatile memory performance, with large memory window, high erase/program current ratio, multilevel data storage ability, stable retention property, and high endurance characteristic.